2014
DOI: 10.1007/s13594-014-0173-6
|View full text |Cite
|
Sign up to set email alerts
|

Heat stability of yak micellar casein as affected by heat treatment temperature and duration

Abstract: International audienceHeat treatment is one of the essential operations widely used in most dairy processes, and heat stability is one of the essential properties of milk. Casein micelles are the major component in milk responsible for the heat stability of milk during processing. This study assessed the effects of heat treatment temperature and duration on the average size, turbidity, polydispersity index and heat stability of casein micelles in yak skim milk and distilled water. The results showed that whey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 33 publications
2
30
1
Order By: Relevance
“…The size of yak casein micelles obtained by ultracentrifugation was larger than that in yak milk, which was 211.3 nm (Yang, Zhang, et al, 2014). It has been reported that the size of casein micelles became more slim with increase of pH whereas it also increased after heat treatment (Erdem, 2006;Yang, Zhang, et al, 2014).…”
Section: Size Of Casein Micellesmentioning
confidence: 83%
See 2 more Smart Citations
“…The size of yak casein micelles obtained by ultracentrifugation was larger than that in yak milk, which was 211.3 nm (Yang, Zhang, et al, 2014). It has been reported that the size of casein micelles became more slim with increase of pH whereas it also increased after heat treatment (Erdem, 2006;Yang, Zhang, et al, 2014).…”
Section: Size Of Casein Micellesmentioning
confidence: 83%
“…It has been reported that the size of casein micelles became more slim with increase of pH whereas it also increased after heat treatment (Erdem, 2006;Yang, Zhang, et al, 2014). Although the size of casein micelles reduced by ultracentrifugation (Sandra & Dalgleish, 2005), it became loose under heat treatment at 40°C with pH 7.0, higher than native pH of milk (6.7), which induced the increase of micellar size.…”
Section: Size Of Casein Micellesmentioning
confidence: 97%
See 1 more Smart Citation
“…Succinylation is one of the frequently used modification method, which enhances solubility, emulsification, foaming characteristics and other functional properties of protein (Gruener & Ismond, 1997;Kohara, Kanei, & Nakajima, 2001;Mirmoghtadaie, Kadivar, & Shahedi, 2009;Yang, Zhang, Wen, Zhang, & Liang, 2014). Succinylation involves chemical derivatization of 3-amino group of lysine in proteins with succinic anhydride.…”
Section: Introductionmentioning
confidence: 99%
“…The high content of β-casein (more than 45%) and consequently the lower proportion of αs-casein (about 40%) together with the high content of κ-casein (15%) in yak milk make it with a good proportion of individual caseins, which is similar to the proportion found in human milk and more favorable for infant nutrition (Li et al 2010). It also found the high content of minerals and micellar size of yak milk (Wang et al 2013;Yang et al 2014b). To develop yak caseins for use as good ingredients in the food industry, their physicochemical and functional properties must be improved.…”
Section: Introductionmentioning
confidence: 84%